Voxelated soft continuum ferromagnetic robot based on thermal drawing - Zhang, Wanting (Nanyang Technological University, 2024)
This thesis provides a comprehensive analysis of the development and technological advancements of magnetic soft robots, from the initial theoretical research to their widespread practical applications. It highlights the crucial technological status of magnetic micro-soft robots in modern industrial and medical fields. This thesis investigates the design, fabrication, and application of voxelized soft continuous ferromagnetic robots created using a thermal drawing process. The primary focus is on developing a magnetic field-driven system using Helmholtz-like coils, aiming to control the magnetic field strength to manipulate magnetic fibers. Additionally, the thesis involves using magnetic fibers with different magnetization directions as the fundamental units of the robots. Experimental demonstrations show the effectiveness of magnetic fibers in precise operation and actuation, attributed to their unique magnetic and physical properties. This research offers insights into material selection and system design in the field of magnetic soft robots. Future work suggests enhancing magnetic field strength and heat dissipation capabilities to expand the practicality and operational range of these robotic systems.